The Impact of Changes in Clinical Guideline on Practice Patterns and Healthcare Utilizations for Kawasaki Disease in Japan - Okubo, Yusuke; Miura, Masaru; Kobayashi, Tohru; Morisaki, Naho; Michihata, Nobuaki; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo (Frontiers in Pediatrics, 2020)
Objective: Previous studies showed the efficacy of glucocorticoids on prevention of coronary artery lesions (CAL) among Kawasaki disease (KD) patients, and clinical guideline for KD in Japan was changed regarding glucocorticoid use in 2012. However, little is known regarding how the guideline change had impacts on healthcare utilizations and clinical outcomes. Methods: We conducted a retrospective observational study using national inpatient database in Japan among KD patients aged under 18 years during 2010–2015. Recent trends in practice patterns were analyzed, and we divided the hospitals into four groups based on glucocorticoid use: (1) consistently using hospital, (2) started using hospital, (3) stopped using hospital, and (4) never using hospital. Then, we compared healthcare utilizations and risks of coronary artery lesions before and after the guideline change. Results: We identified 24,517 inpatients with KD. From 2010 to 2014, use of glucocorticoid increased from 8.9 to 17.4% of KD inpatients. All types of hospitals showed reduction in coronary artery lesions, but the reduction was the most prominent in hospitals that started using glucocorticoid therapy after clinical guideline change in 2012 (adjusted OR, 0.22; 95%CI, 0.07–0.68). Also, Glucocorticoid consistently using hospitals, started using hospitals, and never using hospitals showed reductions in hospitalization costs, whereas hospitals that stopped using glucocorticoids after clinical guideline change had elevated healthcare costs as opposed to natural trends observed in other groups. Guideline complying hospitals had the greatest reductions in healthcare costs. Conclusions: The early stage glucocorticoid use could be a cost-saving strategy for treatment for KD patients without increasing risks of CAL.